Decision Support-Based Energy Benchmarking for Operational Efficiency in FMCG Manufacturing - Rudy Hartono Prayogo; Murpin Josua Sembiring; Damelina Basauli Tambunan (Jurnal Ilmiah Manajemen Kesatuan, 2026)
The Fast-Moving Consumer Goods (FMCG) industry faces increasing pressure to improve operational efficiency due to rising energy costs, intense market competition, and growing sustainability requirements. This study aims to develop and implement a decision support-based energy benchmarking framework to evaluate energy performance, identify efficiency gaps, and support operational improvement initiatives in an FMCG manufacturing facility. A quantitative case study approach was employed using 24 months of operational and energy consumption data collected between January 2023 and December 2024. The analysis utilized normalized energy intensity indicators, comparative performance evaluation, and descriptive statistical benchmarking techniques to assess production output, energy consumption, and energy costs. The results indicate that while production output increased by 30.61%, total energy costs rose disproportionately by 70.66%, revealing significant energy efficiency gaps. Diesel consumption exhibited greater variability than natural gas, contributing substantially to cost fluctuations and highlighting opportunities for operational optimization. The benchmarking results further identified waste heat recovery and energy source optimization as priority improvement strategies. The study concludes that integrating energy benchmarking with decision support principles provides a practical and data-driven framework for enhancing operational efficiency and supporting sustainable energy management in FMCG manufacturing environments.